Laminate and method for manufacturing the same
Patent Information
- Application Number
- JP2023128345
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
AI Technical Summary
【0008】 本発明によると、従来における前記諸問題を解決し、前記目的を達成することができ、耐熱性、熱伝導率、及び接着性に優れる積層体、及び積層体の製造方法を提供することができる。
Smart Images

Figure 2025024317000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a method for producing the laminate. [Background technology]
[0002] In large scale integration (LSI) and the like in various electronic devices, if the LSI itself is exposed to high temperatures for a long period of time due to heat generation from the elements used, this may lead to malfunction or failure. For this reason, thermally conductive materials are widely used to prevent the temperature of LSIs and the like from rising. The thermally conductive materials can prevent the temperature of the equipment from rising by diffusing the heat generated by the elements or by transmitting it to a heat dissipation member for dissipation outside the system, such as the atmosphere.
[0003] When metals or ceramics are used as such thermal conductive materials, there are problems such as difficulty in reducing weight, poor processability, and low flexibility. Therefore, various thermal conductive materials using polymeric materials such as resins or rubbers as a base material have been proposed. For example, a thermal conductive adhesive has been proposed that includes a thermosetting adhesive containing a curing component and a curing agent for the curing component, and a metal filler dispersed in the thermosetting adhesive, the metal filler including silver powder and solder powder, the solder powder having a melting temperature lower than the thermal curing temperature of the thermal conductive adhesive and reacting with the silver powder under the thermal curing conditions of the thermosetting adhesive to produce a high melting point solder alloy having a melting point higher than the melting temperature of the solder powder, the curing agent being a curing agent having flux activity with respect to the metal filler, the curing component being a glycidyl ether type epoxy resin, and the curing agent being a monoanhydride of a tricarboxylic acid (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-188646 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when the metal filler is highly filled in order to achieve high thermal conductivity and low thermal resistance, there is a problem that the fluidity (viscosity) of a composition containing the metal filler deteriorates. On the other hand, when the thermal conductivity is improved by using a low-melting-point metal (solder powder) and bonding between particles with a low-filling metal filler, as in the conventional technology described in Patent Document 1, the amount of low-melting-point metal increases by volume, and high thermal conductivity and low thermal resistance cannot be achieved. In addition, when a low-melting-point metal is used, the thermal conductivity may be significantly affected by the interface material, and when a thermally conductive layer containing a low-melting-point metal is formed on a silicon substrate, the contact resistance with the silicon interface increases, resulting in a decrease in thermal conductivity.
[0006] The present invention aims to solve the above-mentioned problems in the prior art and to achieve the following object: That is, the present invention aims to provide a laminate having excellent heat resistance, thermal conductivity, and adhesiveness, and a method for producing the laminate. [Means for solving the problem]
[0007] The means for solving the above problems are as follows. <1> A substrate; an alloy layer provided on the base material, the alloy layer including an epoxy resin, an epoxy resin curing agent, first thermally conductive particles, and an alloy of a low-melting point metal and the first thermally conductive particles; A laminate having a second thermally conductive layer provided on the alloy layer, the second thermally conductive layer including a hardening component, a hardening agent for hardening the hardening component, second thermally conductive particles, and the low-melting point metal, an area ratio of the alloy layer to the interface of the substrate is 1% or more and 100% or less; The laminate is characterized in that the alloy layer does not contain the low-melting point metal. <2> The heat conductive layer further includes the first heat conductive layer, which contains the epoxy resin, the epoxy resin curing agent, and the first heat conductive particles, and does not contain the low melting point metal. <1> The laminate according to claim 1. <3> The curing agent is represented by at least one of the following general formula (1) and general formula (2): <1> from <2> The laminate according to any one of claims 1 to 5, [ka] In the general formula (1), R1 to R3 each independently represent a hydrogen atom, an alkyl group, or a caprolactone skeleton, R4 represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group, and R5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms. [ka] In the general formula (2), R1 and R2 each independently represent a hydrogen atom, an alkyl group, or a caprolactone skeleton. R4 and R6 each independently represent a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group. R5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms. <4> The curing component includes at least one of an oxetane compound and an epoxy resin. <1> from <3> The laminate according to any one of claims 1 to 5, <5> The first thermally conductive particles include at least one of silver particles, silver-coated particles, and silver particles. <1> from <4> The laminate according to any one of claims 1 to 5, <6> The low melting point metal includes Sn and at least one selected from Bi, Ag, Cu, and In. <1> from <5> The laminate according to any one of claims 1 to 5, <7> The substrate includes at least one material selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics. <1> from <6> The laminate according to any one of claims 1 to 5, <8> The content of the first thermally conductive particles in the first thermally conductive layer is 50% by volume or more. <1> from <7> The laminate according to any one of claims 1 to 5, <9> a facing substrate on the second thermally conductive layer, the facing substrate facing the substrate; The opposing substrate contains at least one selected from the group consisting of copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. <1> from <8> The laminate according to any one of claims 1 to 5, <10> applying a first thermally conductive layer composition onto a substrate, the first thermally conductive layer composition including an epoxy resin, an epoxy resin curing agent, and first thermally conductive particles; applying a second thermally conductive layer composition onto the applied first thermally conductive layer composition, the second thermally conductive layer composition including a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting point metal particles; and heating the first thermally conductive layer composition and the second thermally conductive layer composition to form an alloy layer formed by the low-melting point metal of the low-melting point metal particles melting and reacting with the first thermally conductive particles, and a second thermally conductive layer. The method for producing a laminate is characterized in that the area ratio of the alloy layer to the interface of the base material is 1% or more and 100% or less. Effect of the Invention
[0008] According to the present invention, it is possible to solve the above-mentioned problems in the conventional art and achieve the above-mentioned object, thereby providing a laminate having excellent heat resistance, thermal conductivity, and adhesiveness, and a method for producing the laminate. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of a process for producing a laminate according to this embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a laminate according to this embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing another example of the laminate according to the present embodiment. [Figure 4] FIG. 4 is a schematic diagram showing another example of the laminate according to the present embodiment. [Diagram 5]FIG. 5 is a schematic cross-sectional view showing an example of a heat dissipation structure having the laminate of the present embodiment. [Figure 6] FIG. 6 is a schematic cross-sectional view showing the substrate interface of the laminate of Example 1. As shown in FIG. [Figure 7] FIG. 7 is a schematic cross-sectional view showing the substrate interface of the laminate of Example 2. As shown in FIG. [Figure 8] FIG. 8 is a schematic cross-sectional view showing the substrate interface of the laminate of Example 3. [Figure 9] FIG. 9 is a schematic cross-sectional view showing the substrate interface of the laminate of Example 4. [Figure 10] FIG. 10 is a schematic cross-sectional view showing the substrate interface of the laminate of Example 5. [Figure 11] FIG. 11 is a schematic cross-sectional view showing the substrate interface of the laminate of Comparative Example 1. As shown in FIG. [Figure 12] FIG. 12 is a schematic diagram showing the laminate of Comparative Example 1. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Laminate) The laminate of the present invention comprises a substrate, an alloy layer, and a second thermally conductive layer, and may further comprise other members such as a first thermally conductive layer, if necessary.
[0011] The laminate of the present embodiment has an alloy layer and a second thermally conductive layer in this order on a substrate, the alloy layer being an alloy layer containing an epoxy resin, an epoxy resin curing agent, first thermally conductive particles, and an alloy of a low-melting point metal and the first thermally conductive particles, and the area ratio of the alloy layer to the interface of the substrate is 1% or more and 100% or less, thereby providing a laminate having excellent heat resistance, thermal conductivity, and adhesion. In the manufacturing process of the laminate, a curing agent having flux activity and a molten low-melting point metal contained in the second thermally conductive layer composition laminated on the upper layer flow into the first thermally conductive layer composition for forming the lower layer, and the first thermally conductive particles contained in the first thermally conductive layer composition react with the flowed low-melting point metal to form an alloy, thereby forming the alloy layer.
[0012] <Base material> The shape, structure, size, material, etc. of the substrate are not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape of the substrate include a plate shape, a sheet shape, etc. Examples of the structure of the substrate include a single-layer structure, a laminated structure, etc. The size of the substrate can be appropriately selected depending on the application, etc.
[0013] As the material for the substrate, a material that is difficult for solder to wet can be selected because the alloy layer in contact with the substrate and the optional first thermal conduction layer do not contain a low-melting point metal. Suitable examples of the material for the substrate include silicon, aluminum, tungsten, molybdenum, glass, molded resin, stainless steel, and ceramics. Examples of the ceramics include aluminum nitride, silicon carbide, alumina, and gallium nitride. Examples of the molding resin include epoxy resin, silicone resin, urethane resin, and acrylic resin. The substrate preferably comprises silicon.
[0014] The average thickness of the substrate is not particularly limited and can be appropriately selected depending on the purpose. The substrate may be the heat generating body (electronic component) itself in the heat dissipation structure.
[0015] <Alloy layer> The alloy layer is formed on the substrate and forms an interface with the substrate, and an area ratio of the alloy layer to the interface with the substrate is 1% or more and 100% or less. The alloy layer contains an epoxy resin, an epoxy resin curing agent for curing the epoxy resin, first thermally conductive particles, an alloy of a low-melting point metal and the first thermally conductive particles, and may further contain other components as necessary. The first thermally conductive layer does not contain a low-melting point metal.
[0016] -Epoxy resin- The epoxy resin is a resin having an epoxy group (oxirane ring) in the polymer, and is a thermosetting resin that can be cured by forming a crosslink via the epoxy group. By including an epoxy resin in the first thermally conductive layer, flexibility can be imparted, and thermal conductivity and adhesiveness, particularly after a reflow treatment, can be achieved, and therefore excellent heat resistance can be achieved. Examples of the epoxy resin include glycidyl ether type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, trisphenol type epoxy resin, tetraphenol type epoxy resin, phenol-xylylene type epoxy resin, naphthol-xylylene type epoxy resin, phenol-naphthol type epoxy resin, phenol-dicyclopentadiene type epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, etc. These may be used alone or in combination of two or more.
[0017] Among the above epoxy resins, glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, phenol-dicyclopentadiene type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, and aliphatic epoxy resins are preferred. A suitable example of a commercially available bisphenol A type epoxy resin is EPICLON (registered trademark) EXA-850CRP (manufactured by DIC Corporation).
[0018] The content of the epoxy resin is preferably 5 vol% to 50 vol%, more preferably 10 vol% to 40 vol%, and even more preferably 20 vol% to 40 vol%, based on the total amount of the first thermally conductive layer.
[0019] -Epoxy resin hardener- The epoxy resin curing agent is a curing agent that cures the epoxy resin, and examples thereof include polyaddition type curing agents such as acid anhydride-based curing agents, aliphatic amine-based curing agents, aromatic amine-based curing agents (e.g., imidazole-based curing agents), phenol-based curing agents, and mercaptan-based curing agents; and catalyst type curing agents such as imidazole. These may be used alone or in combination of two or more. Among these, aromatic amine-based curing agents are preferred, and imidazole-based curing agents are more preferred.
[0020] As the imidazole-based curing agent, a commercially available product can be used. Examples of the commercially available product include HX-3941HP, HXA3922HP, HXA3792, HXA3932HP, HXA3042HP, HXA9322HP, HXA9382HP, HXA5052HP, and HXA3542HP from the "Novacure (registered trademark)" series sold by Asahi Chemical Industry Co., Ltd. The Novacure® series is a microcapsule-type liquid latent curing agent for epoxy resin, and by varying the capsule thickness and capsule particle size, it is possible to adjust the curing start temperature, reaction rate, and solvent resistance of the first thermal conductive layer composition for forming the first thermal conductive layer. The Novacure® series also contains uncured epoxy resins of bisphenol A type and bisphenol F type, and when the temperature becomes high (around 100°C), the curing agent is released from the capsule into the bulk (liquid epoxy resin), and the curing proceeds. The curing initiation temperature of the epoxy resin curing agent is preferably 120° C. or higher.
[0021] The content of the epoxy resin curing agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1 volume % or more and 20 volume % or less, more preferably 1 volume % or more and 10 volume % or less, and even more preferably 3 volume % or more and 5 volume % or less, based on the total amount of the first thermal conductive layer.
[0022] -First thermally conductive particle- The first thermally conductive particles are preferably at least any one of copper particles, silver-coated particles, and silver particles, and more preferably silver particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the first thermally conductive particles is not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes.
[0023] The content of the first thermally conductive particles in the alloy layer is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoint of achieving high packing and improving thermal conductivity, however, the content is preferably 40 volume % or more, more preferably 45 volume % or more, and even more preferably 50 volume % or more.
[0024] The volume average particle diameter of the first thermally conductive particles is preferably 0.3 μm to 30 μm, more preferably 0.5 μm to 10 μm. When the volume average particle diameter of the thermally conductive particles is 0.3 μm to 30 μm, the volume ratio of the first thermally conductive particles to the low-melting point metal particles can be increased, and the laminate can have excellent heat resistance, thermal conductivity, and adhesiveness. The volume average particle size can be measured, for example, by a laser diffraction / scattering type particle size distribution measuring device (product name: Microtrac MT3300EXII).
[0025] -Low melting point metal- The alloy layer does not contain a low melting point metal. Here, the low-melting point metal refers to the low-melting point metal particles described in the second thermal conductive layer composition in the laminate manufacturing method described below, and the low-melting point metal formed by melting and solidifying the low-melting point metal particles.
[0026] The low melting point metal flowing into the first thermally conductive layer composition for forming the alloy layer is alloyed with the first thermally conductive layer particles to form an alloy. The form of the alloy to be formed is not particularly limited and can be appropriately selected depending on the purpose. Examples of the alloy include substitutional solid solutions, interstitial solid solutions, intermetallic compounds, and eutectic alloys. Other examples include an embodiment in which the surface of the first thermally conductive particle is alloyed and the surface of the first thermally conductive particle is coated with an alloy; and an embodiment in which the entire first thermally conductive particle is alloyed. Although any of these embodiments may exist, the embodiment in which the surface of the first thermally conductive particle is coated with an alloy may predominate.
[0027] The method for confirming that the alloy layer does not contain the low-melting point metal is not particularly limited and can be appropriately modified depending on the purpose. For example, a method of polishing a cut surface of the laminate and observing the polished surface with a scanning electron microscope (e.g., S-3000N, manufactured by Hitachi, Ltd.), or a method of analyzing by the analysis method described in the Japanese Industrial Standard JIS Z 3910:2017 Solder Analysis Method can be used.
[0028] -Other ingredients- The alloy layer may contain other components as long as the effect of the present invention is not impaired. The other components are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include thermally conductive particles other than metals (e.g., aluminum nitride, alumina, carbon fiber, etc.), additives (e.g., antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc.), and resins other than epoxy resins.
[0029] The resin other than the epoxy resin is not particularly limited and can be appropriately selected depending on the purpose. Examples of the resin include a polymer having at least one structure selected from a phenoxy structure, a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polyamide structure, and a polycarbonate structure in the molecule.
[0030] The first thermally conductive layer composition for forming the alloy layer can be prepared by uniformly mixing the epoxy resin, the epoxy resin curing agent, the first thermally conductive particles, and other components as necessary, by a conventional method.
[0031] The average thickness of the alloy layer is not particularly limited and may be appropriately selected depending on the purpose, but is preferably from 1 μm to 100 μm, and more preferably from 5 μm to 50 μm.
[0032] [Area ratio of alloy layer to substrate interface] The area ratio of the alloy layer to the interface of the substrate is 1% or more and 100% or less, and preferably 5% or more and 100% or less. The interface of the substrate means the interface between the substrate and the alloy layer, the first thermally conductive layer, or the resin layer described later, and may be the entire surface of one surface of the substrate, or a partial region of one surface of the substrate.
[0033] The area of the interface of the substrate, the area of the alloy layer relative to the interface of the substrate, and the area ratio can be measured by the following procedure: Measurements are performed by utilizing the property of infrared rays penetrating substrates such as silicon, germanium, calcium fluoride, N-BK7, potassium bromide, potassium bromide, zinc selenide, zinc sulfide, and sapphire.
[0034] The interface between the substrate and the thermally conductive layer, which is the cured product of the thermally conductive composition, was photographed from the substrate side of the laminate using an infrared microscope (MX63, manufactured by Olympus Corporation) and an InGaAs camera (C12741-03, manufactured by Hamamatsu Photonics Co., Ltd.) The image of the alloy layer, i.e., the alloyed portion where the alloy is formed, was binarized to distinguish it from the other portions, and the area of the alloy layer was calculated. The area in the image is calculated using Excel made by Microsoft Corp. The binary bitmap image created is loaded into Excel, the number of pixels in the entire image corresponding to the area of the substrate interface and the number of pixels in the alloyed part corresponding to the area of the alloy layer are obtained, and the area ratio (%) of the alloy layer to the substrate interface is calculated based on the following formula (1). (Formula 1) Area ratio of alloy layer to substrate interface (%) = (Number of pixels in alloyed area / total number of pixels) x 100
[0035] <Second heat conductive layer> The second thermally conductive layer contains a curable component, a curing agent that cures the curable component, second thermally conductive particles, and a low-melting point metal, and further contains other components as necessary.
[0036] -Curing component- The curing component preferably contains at least one of an oxetane compound and an epoxy resin, and more preferably contains an oxetane compound and an epoxy resin.
[0037] --Oxetane compounds-- The oxetane compound is a compound having an oxetanyl group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound. The oxetane compound may be a monofunctional oxetane compound having only one oxetanyl group, or a polyfunctional oxetane compound having two or more oxetanyl groups.
[0038] The oxetane compound is not particularly limited and can be appropriately selected depending on the purpose. Examples of the oxetane compound include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4 -bis(3-ethyl-3-oxetanylmethoxy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylenebisoxetane, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), etc. These may be used alone or in combination of two or more.
[0039] As the oxetane compound, commercially available products can be used. Examples of the commercially available products include the "ARON OXETANE (registered trademark)" series sold by Toagosei Co., Ltd. and the "ETERNACOLL (registered trademark)" series sold by Ube Industries, Ltd. Among these, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (ETERNACOLL (registered trademark) OXBP) is preferred.
[0040] --Epoxy resin-- The epoxy resin is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A type epoxy resins, trisphenol type epoxy resins, tetraphenol type epoxy resins, phenol-xylylene type epoxy resins, naphthol-xylylene type epoxy resins, phenol-naphthol type epoxy resins, phenol-dicyclopentadiene type epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. These may be used alone or in combination of two or more.
[0041] The content of the curing component is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by volume or more and 60% by volume or less based on the total amount of the second thermally conductive layer.
[0042] - Hardener - The curing agent is a curing agent corresponding to the curing component, and examples thereof include polyaddition type curing agents such as polyfunctional carboxylic acid, acid anhydride type curing agent, aliphatic amine type curing agent, aromatic amine type curing agent, phenol type curing agent, and mercaptan type curing agent, and catalyst type curing agents such as imidazole. These may be used alone or in combination of two or more.
[0043] Among these, polyfunctional carboxylic acids are preferred, and polyfunctional carboxylic acids represented by at least one of the following general formulas (1) and (2) are more preferred.
[0044] [ka] In the general formula (1), R1 to R3 each independently represent a hydrogen atom, an alkyl group, or a caprolactone skeleton, R4 represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group, and R5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.
[0045] [ka] In the general formula (2), R1 and R2 each independently represent a hydrogen atom, an alkyl group, or a caprolactone skeleton. R4 and R6 each independently represent a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group. R5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.
[0046] The alkyl group in R1 to R3 in the general formula (1) and R1 and R2 in the general formula (2) is preferably an alkyl group having 1 to 10 carbon atoms, and examples thereof include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a hexyl group, a heptyl group, an octyl group, a 2-ethylhexyl group, a tert-octyl group, and a cyclohexyl group. The caprolactone skeleton in R1 to R3 in the general formula (1) and R1 and R2 in the general formula (2) is represented by the following general formula (i). [ka] In the general formula (i), n represents an integer of 1 or more, and preferably an integer of 1 to 10. m represents an integer of 2 or more, and preferably an integer of 2 to 5.
[0047] Examples of the alkyl group which may be substituted with a hydroxyl group in R4 and R6 include a methyl group, an ethyl group, a propyl group, -(CH2)-OH, -(CH2)2-OH, and -(CH2)3-OH.
[0048] Examples of the alkyl group having 1 to 3 carbon atoms for R5 include a methyl group, an ethyl group, a propyl group, and an isopropyl group. Examples of the alkenyl group having 2 to 3 carbon atoms for R5 include a vinyl group, a 1-propenyl group, and an allyl group (2-propenyl group). R5 is preferably either an alkyl group having 2 to 3 carbon atoms or an alkenyl group having 2 carbon atoms, from the viewpoint of combining excellent flux activity and curability.
[0049] The polyfunctional carboxylic acid represented by at least one of the general formula (1) and the general formula (2) can be synthesized by reacting a specific acid anhydride with a specific polyfunctional alcohol, as described below.
[0050] [Method of producing polyfunctional carboxylic acid] The method for producing the polyfunctional carboxylic acid includes a step of esterifying an acid anhydride with a polyfunctional alcohol, and further includes other steps as necessary. The esterification reaction between the acid anhydride and the polyfunctional alcohol is not particularly limited and can be appropriately selected depending on the purpose.
[0051] Examples of the acid anhydride include succinic anhydride, glutaric anhydride, maleic anhydride, phthalic anhydride, benzoic anhydride, oxalic anhydride, etc. These may be used alone or in combination of two or more. Among these, succinic anhydride, glutaric anhydride, and maleic anhydride are preferred.
[0052] The polyfunctional alcohol is preferably difunctional or more, more preferably difunctional or more and tetrafunctional or less. Examples of the polyfunctional alcohol include caprolactone derivatives, glycerin, ethylene glycol, and propylene glycol. These may be used alone or in combination of two or more. Of these, caprolactone derivatives and glycerin are preferred.
[0053] The caprolactone derivatives include compounds having a caprolactone skeleton represented by the general formula (i) above. As the caprolactone derivative, commercially available products can be used, and examples of the commercially available products include PLACCEL 205, PLACCEL 205U, PLACCEL 303, and PLACCEL 410 (all manufactured by Daicel Corporation).
[0054] An example of an esterification reaction between a specific acid anhydride and a trifunctional alcohol is shown below. [ka] In the above reaction formula, R1 to R3 represent a hydrogen atom, an alkyl group, or a caprolactone skeleton, R4 represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group, and R5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.
[0055] The other steps are not particularly limited and can be appropriately selected depending on the purpose. For example, a concentration step, a separation and purification step, etc. can be mentioned.
[0056] The polyfunctional carboxylic acid represented by at least one of the general formulas (1) and (2) can achieve both a good flux effect and a good function as a curing agent. That is, the polyfunctional carboxylic acid represented by at least one of the general formulas (1) and (2) is liquid from room temperature to high temperature, and does not react during film formation, so that it can improve the wettability of the coating liquid. When heated in stages, it exerts a flux effect by heating in the first stage, and then has a heat curing start switch function that starts curing by the curing components that were mixed together by heating in the second stage. The heating temperature in the first stage is preferably 120°C to 150°C, for example. The heating temperature in the second stage is preferably 150°C to 190°C, for example.
[0057] The polyfunctional carboxylic acid is preferably liquid at 25°C and 150°C. Here, being liquid means having fluidity that allows application. The fact that the polyfunctional carboxylic acid is liquid at 25° C. and 150° C. can be confirmed, for example, by visually confirming the fluidity at 25° C. (room temperature) and by the presence or absence of an absorption peak up to 150° C. by DSC. The molecular weight of the polyfunctional carboxylic acid is preferably 800 g / mol or less, more preferably 400 g / mol or more and 700 g / mol or less, in view of being liquid. The molecular weight of the polyfunctional carboxylic acid can be measured, for example, by Shodex (registered trademark) GPC-101 (a product of Showa Denko K.K.).
[0058] The polyfunctional carboxylic acid is a curing agent having flux activity. The first-stage heating causes the polyfunctional carboxylic acid to have flux activity, which can improve the wettability of the molten low-melting metal to the second thermally conductive particles contained in the second thermally conductive layer. In addition, the polyfunctional carboxylic acid in excess of the amount required for forming the second thermally conductive layer, which is the upper layer, flows into the first thermally conductive layer composition for forming the lower layer together with the molten low-melting metal, and reacts with the first thermally conductive particles contained in the first thermally conductive layer composition to form an alloy layer. Then, by heating in a second stage, the polyfunctional carboxylic acid can cure the curing components in each of the second thermally conductive layer, the alloy layer, and the first thermally conductive layer. By forming the alloy layer, the heat resistance of the resulting laminate can be improved.
[0059] The acid anhydride-based curing agent is preferred in that, when the curing component is an epoxy resin, no gas is generated during thermal curing, a long pot life can be achieved when mixed with the epoxy resin, and a good balance can be achieved between the electrical properties, chemical properties, and mechanical properties of the resulting cured product.
[0060] Examples of the acid anhydride curing agent include cyclohexane-1,2-dicarboxylic anhydride, monoacid anhydrides of tricarboxylic acids, etc. Examples of the monoacid anhydrides of tricarboxylic acids include cyclohexane-1,2,4-tricarboxylic-1,2-acid anhydride, etc.
[0061] The curing agent preferably has flux activity, from the viewpoint of improving the wettability of the molten low-melting point metal to the thermally conductive particles. Examples of methods for making the curing agent exhibit flux activity include methods of introducing protonic acid groups such as carboxyl groups, sulfonyl groups, and phosphoric acid groups into the curing agent by known methods. Among these, it is preferable to introduce a carboxyl group from the viewpoint of reactivity with the epoxy resin or oxetane compound as the curing component, and examples thereof include organic acids containing a carboxyl group such as glutaric acid and succinic acid. In addition, compounds modified from glutaric anhydride or succinic anhydride, or metal salts of organic acids such as silver glutarate may also be used.
[0062] The content of the curing agent in the second thermally conductive layer is an amount that is in excess of the amount necessary to form the second thermally conductive layer, which is the upper layer, and can be appropriately selected so that an alloy layer can be formed together with the first thermally conductive particles contained in the first thermally conductive layer composition for forming the lower layer, and is preferably 10 vol. % or more and 20 vol. % or less, and more preferably 15 vol. % or more and 19 vol. % or less, relative to the total amount of the second thermally conductive layer.
[0063] -Second thermally conductive particle- The second thermally conductive particles are preferably at least any one of copper particles, silver-coated particles, and silver particles, and more preferably silver-coated particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the second thermally conductive particles is not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes.
[0064] The volume average particle diameter of the second thermally conductive particles is preferably 1 μm or more and 100 μm or less, more preferably 5 μm or more and 70 μm or less, and even more preferably 5 μm or more and 50 μm or less. When the volume average particle diameter of the second thermally conductive particles is 1 μm or more and 100 μm or less, excellent thermal conductivity can be achieved. The volume average particle size of the second thermally conductive particles can be measured in the same manner as the volume average particle size of the first thermally conductive particles.
[0065] -Low melting point metal- The low melting point metal means the low melting point metal particles and the low melting point metal formed by melting and solidifying the low melting point metal particles. As the low melting point metal particles, solder particles as specified in JIS Z3282-1999 are preferably used.
[0066] Examples of the solder particles include Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, Sn-Ag-Cu solder particles, etc. These may be used alone or in combination of two or more. Among these, solder particles containing Sn and at least one selected from Bi, Ag, Cu, and In are preferred, Sn-Bi based solder particles, Sn-Bi-Ag based solder particles, Sn-Ag-Cu based solder particles, and Sn-In based solder particles are more preferred, and Sn-Bi based solder particles containing Sn and Bi are even more preferred.
[0067] The shape of the low melting point metal particles is not particularly limited and may be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes. The melting point of the low-melting-point metal particles is preferably 100°C or higher and 250°C or lower, and more preferably 120°C or higher and 200°C or lower.
[0068] The melting point of the low-melting point metal particles is preferably lower than the thermal curing temperature (second-stage heating) of the first thermal conductive layer composition and the second thermal conductive layer composition. This allows the formation of a second thermally conductive layer in which a network (continuous metal phase) is formed through the second thermally conductive particles by the low-melting-point metal melted in the cured product of the second thermally conductive layer composition. In addition, an excess amount of curing agent, which is more than the amount required for forming the upper layer, flows into the first thermally conductive layer composition for forming the lower layer together with the melted low-melting-point metal particles, and reacts with the first thermally conductive particles contained in the first thermally conductive layer composition to form an alloy layer. Therefore, a laminate with excellent heat resistance, thermal conductivity, and adhesiveness can be realized. The low-melting point metal reacts with the first thermally conductive particles under the thermal curing treatment conditions of the first thermally conductive layer composition to form an alloy having a higher melting point than the low-melting point metal particles, thereby achieving excellent thermal conductivity and adhesion of the laminate not only after compression bonding but also after reflow treatment, and therefore excellent heat resistance. The heat curing treatment of the first thermal conductive layer composition is carried out under conditions of, for example, a temperature of 150° C. to 190° C. for 30 minutes to 2 hours.
[0069] The volume average particle diameter of the low-melting metal particles is preferably 10 μm or less, more preferably 1 μm or more and 5 μm or less. When the volume average particle diameter of the low-melting metal particles is 10 μm or less, the volume ratio of the low-melting metal particles to the second thermal conductive particles can be reduced, and high thermal conductivity and low thermal resistance of the second thermal conductive layer can be achieved. The volume average particle size of the low-melting point metal particles can be measured in the same manner as the volume average particle size of the first thermally conductive particles.
[0070] The volume average particle size of the second thermally conductive particles is larger than the volume average particle size of the low-melting point metal particles, and the volume average particle size ratio (A / B) of the second thermally conductive particles A to the low-melting point metal particles B is preferably 2 or more, more preferably 3 or more, and even more preferably 5 or more. The upper limit of the volume average particle size ratio (A / B) is preferably 20 or less, and more preferably 10 or less. By using low-melting point metal particles having a smaller volume average particle size than the second thermally conductive particles, the second thermally conductive particles become the main component in the second thermally conductive layer composition, and the low-melting point metal particles present between the second thermally conductive particles and the second thermally conductive particles melt when heated and alloy with the second thermally conductive particles to form a network, thereby achieving high thermal conductivity and low thermal resistance.
[0071] In the second thermally conductive layer composition for forming the second thermally conductive layer, the volume ratio (A / B) of the second thermally conductive particles A to the low-melting point metal particles B is preferably at least 1, more preferably at least 1.5, and even more preferably at least 2. The upper limit of the volume ratio (A / B) is preferably at most 5, more preferably at most 4, and even more preferably at most 3.
[0072] The average thickness of the second thermally conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 20 μm to 300 μm, and more preferably from 50 μm to 200 μm.
[0073] <First thermal conductive layer> The laminate may have the first thermally conductive layer at the interface with the substrate, so long as the area ratio of the alloy layer to the interface with the substrate is in the range of 1% to 100%. The first thermally conductive layer contains the epoxy resin, the epoxy resin curing agent, and the first thermally conductive particles, and further contains other components as necessary. The first thermally conductive layer is a layer that does not contain the low-melting point metal and the alloy.
[0074] The average thickness of the alloy layer is not particularly limited and may be appropriately selected depending on the purpose, but is preferably from 1 μm to 30 μm, and more preferably from 5 μm to 30 μm. The average thickness of the alloy layer can be appropriately set by adjusting the content of the curing agent and the content of the low-melting point metal particles contained in the second thermally conductive layer composition.
[0075] The method for confirming that the first thermally conductive layer does not contain the low-melting point metal is not particularly limited and can be appropriately modified depending on the purpose. For example, a method of polishing a cut surface of the laminate and observing the polished surface with a scanning electron microscope (e.g., S-3000N, manufactured by Hitachi, Ltd.), or a method of analyzing by the analysis method described in the Japanese Industrial Standard JIS Z 3910:2017 Solder Analysis Method can be used.
[0076] <Facing substrate> The opposing substrate is disposed opposite the substrate, and its shape, structure, size, material, etc. are not particularly limited and can be appropriately selected depending on the purpose. The shape of the opposing substrate may be, for example, a plate shape, a sheet shape, etc. The structure of the opposing substrate may be, for example, a single-layer structure, a laminated structure, etc. The size of the opposing substrate may be appropriately selected depending on the application, etc. The material of the facing base material is a material that is easily wetted by solder, and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the purpose. The opposing base material may be the heat spreader itself in the heat dissipation structure.
[0077] <Other materials> The other members are not particularly limited and can be appropriately selected depending on the purpose. For example, a protective layer can be mentioned.
[0078] (Method of manufacturing laminate) The method for producing a laminate of the present invention includes a first applying step, a second applying step, and a heating step, and may further include other steps as necessary.
[0079] <First application step> The first applying step is a step of applying a first thermally conductive layer composition onto the substrate. The first thermally conductive layer composition contains an epoxy resin, an epoxy resin curing agent, and first thermally conductive particles, does not contain a low-melting point metal, and may further contain other components as necessary. The base material, epoxy resin, epoxy resin curing agent, first thermally conductive particles, other components, and low-melting point metal can be appropriately selected from the items described in the laminate of this embodiment.
[0080] Examples of methods for applying the first thermal conductive layer composition to the substrate include an inkjet method, a blade coating method, a gravure coating method, a gravure offset coating method, a bar coating method, a roll coating method, a knife coating method, an air knife coating method, a comma coating method, a U comma coating method, an AKKU coating method, a smoothing coating method, a microgravure coating method, a reverse roll coating method, a four-roll coating method, a five-roll coating method, a dip coating method, a curtain coating method, a slide coating method, and a die coating method.
[0081] <Second applying step> The second applying step is a step of applying a second thermally conductive layer composition onto the applied first thermally conductive layer composition. The second thermally conductive layer composition contains a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting point metal particles, and further contains other components as necessary. The second curing component, the second curing agent, the second thermally conductive particles, and the low-melting point metal particles can be appropriately selected from the items described in the laminate of this embodiment.
[0082] Examples of a method for applying the second thermal conductive layer composition onto the first thermal conductive layer composition include an inkjet method, a blade coating method, a gravure coating method, a gravure offset coating method, a bar coating method, a roll coating method, a knife coating method, an air knife coating method, a comma coating method, a U comma coating method, an AKKU coating method, a smoothing coating method, a microgravure coating method, a reverse roll coating method, a four-roll coating method, a five-roll coating method, a dip coating method, a curtain coating method, a slide coating method, and a die coating method.
[0083] <Heating process> The heating process is a process of heating the first thermally conductive layer composition and the second thermally conductive layer composition to form an alloy layer in which the low-melting point metal from which the low-melting point metal particles are dissolved reacts with the first thermally conductive particles, and a second thermally conductive layer.
[0084] The heating conditions are preferably as follows: (1) a first-stage heating in which the flux activity of the curing agent is expressed, and the curing agent and the dissolved low-melting point metal flow into the first thermal conductive layer composition; and (2) a second-stage heating in which the curing activity of the curing agent is expressed, and each layer is cured. The heating may be performed, for example, by continuously increasing the temperature to perform a first heating step and then a second heating step, or two heating steps may be performed sequentially. The heating in the first stage is preferably performed at 120° C. to 150° C. for 1 minute to 30 minutes, for example. The second stage of heating is preferably carried out at 150° C. to 190° C. for 30 minutes to 2 hours.
[0085] The second thermally conductive layer composition is applied onto the first thermally conductive layer composition while still in the liquid phase, and then the flux activity of the curing agent is expressed by a first heating step, whereby the curing agent having flux activity and the molten low-melting point metal contained in the second thermally conductive layer composition laminated on the upper layer flow into the first thermally conductive layer composition for forming the lower layer.
[0086] Then, the second thermal conductive layer composition is cured by the second heating step to form a second thermal conductive layer, and the first thermal conductive particles contained in the first thermal conductive layer composition react with the low melting point metal to form an alloy, thereby forming the alloy layer. The substrate and the alloy layer form an interface, and the obtained laminate may have a first thermally conductive layer between the substrate and the alloy layer, the first thermally conductive layer being formed by curing the first thermally conductive layer composition.
[0087] The curing initiation temperature of the epoxy resin curing agent is preferably 120° C. or higher. When the curing start temperature is 120° C. or higher, after the second application step and during the first stage of the heating step, the first thermal conductive layer composition does not start curing, and the flux activity of the curing agent is expressed, causing the curing agent and the molten low-melting point metal to flow into the first thermal conductive layer composition. The subsequent second stage of heating causes each layer to be cured, and an alloy layer is suitably formed.
[0088] <Other processes> The other steps are not particularly limited and may be appropriately selected depending on the purpose. For example, a protective layer forming step, an opposing substrate laminating step, and the like may be included.
[0089] Here, the laminate manufacturing method and the laminate according to the present invention will be described in detail with reference to the drawings. In each drawing, the same components are denoted by the same reference numerals, and duplicated descriptions may be omitted. In addition, the number, position, shape, etc. of the following components are not limited to the present embodiment, and may be any number, position, shape, etc. that is preferable for implementing the present invention.
[0090] FIG. 1 is a schematic diagram showing an example of a process for producing a laminate according to an embodiment. The uncured laminate 10a shown in FIG. 1 is a wet-on-wet uncured laminate after the second application step and before the heating step, and specifically has a first thermally conductive layer composition 12a containing first thermally conductive particles 12b on a substrate 11, a second thermally conductive layer composition 14a containing second thermally conductive particles 14b and low-melting point metal particles 14c on the first thermally conductive layer composition 12a, and an opposing substrate 15 on the second thermally conductive layer composition 14a.
[0091] FIG. 2 is a schematic diagram illustrating an example of a laminate according to an embodiment. The laminate 10 shown in FIG. 2 has an alloy layer 13 containing an alloy 13b on a substrate 11, a second thermally conductive layer 14 containing second thermally conductive particles 14b and a low-melting point metal 14d on the alloy layer 13, and an opposing substrate 15 on the second thermally conductive layer 14. The area ratio of the alloy layer 13 to the interface of the substrate 11 is 1% or more and 100% or less.
[0092] 3 and 4 are schematic diagrams showing another example of the laminate according to the embodiment. When the area ratio of the alloy layer 13 to the interface of the substrate 11 is less than 100%, the laminate 10 may further have a first thermally conductive layer 12 containing first thermally conductive particles 12b between the substrate layer 11 and the alloy layer 13, as shown in FIG. 3, or may further have a resin layer 16 derived from excess curing agent flowing in from the second thermally conductive layer composition between the substrate layer 11 and the alloy layer 13, as shown in FIG. 4.
[0093] The laminate of the present invention can be suitably used, for example, as a thermal interface material (TIM) that fills the minute gap between a heat source such as an LSI and a heat sink, thereby allowing heat to flow smoothly between the two, or when adhering a heat dissipation substrate mounting an LED chip or an IC chip to a heat sink to form a power LED module or a power IC module. Here, the power LED module is classified into a wire bonding mounting type and a flip chip mounting type, and the power IC module is classified into a wire bonding mounting type.
[0094] (heat dissipation structure) The heat dissipation structure of the present embodiment includes a heat generating body, the above-described laminate of the present invention, and a heat dissipation member, and further includes other members as necessary.
[0095] The heating element is not particularly limited and can be appropriately selected depending on the purpose. Examples of the heating element include electronic components such as a central processing unit (CPU), a micro processing unit (MPU), and a graphics processing unit (GPU).
[0096] The heat dissipation member is not particularly limited as long as it is a structure that dissipates heat generated by an electronic component (heat generating element), and can be appropriately selected depending on the purpose. Examples of the heat dissipation member include a heat spreader, a heat sink, a vapor chamber, and a heat pipe. The heat spreader is a member for efficiently transferring heat from the electronic component to other components. The material of the heat spreader is not particularly limited and can be appropriately selected depending on the purpose, and examples of the material include copper and aluminum. The heat spreader is usually in a flat plate shape. The heat sink is a member for releasing heat from the electronic component into the air. The material of the heat sink is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include copper and aluminum. The heat sink has, for example, a plurality of fins. The heat sink has, for example, a base portion and a plurality of fins provided so as to extend in a non-parallel direction (for example, a direction perpendicular to) one surface of the base portion. The heat spreader and the heat sink are generally solid structures with no internal voids. The vapor chamber is a hollow structure. A volatile liquid is sealed in the internal space of the hollow structure. Examples of the vapor chamber include a hollow structure of the heat spreader, a hollow plate-shaped structure of the heat sink, and the like. The heat pipe is a hollow structure having a cylindrical, approximately cylindrical, or flattened tubular shape, and a volatile liquid is sealed in the internal space of the hollow structure.
[0097] Here, Fig. 5 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates heat generated by an electronic component 3 such as a semiconductor element, and is fixed to a main surface 2a of a heat spreader 2 facing the electronic component 3, as shown in Fig. 5, and is sandwiched between the electronic component 3 and the heat spreader 2. In addition, a thermally conductive sheet 1 is sandwiched between the heat spreader 2 and a heat sink 5.
[0098] The heat spreader 2 is formed, for example, in the shape of a rectangular plate, and has a main surface 2a facing the electronic component 3, and a side wall 2b erected along the outer periphery of the main surface 2a. The heat spreader 2 has a thermally conductive sheet 1 provided on the main surface 2a surrounded by the side wall 2b, and a heat sink 5 provided on the other surface 2c opposite the main surface 2a via the thermally conductive sheet 1. The higher the thermal conductivity of the heat spreader 2, the lower the thermal resistance and the more efficiently it absorbs heat from the electronic component 3 such as a semiconductor element, so the heat spreader 2 can be formed, for example, using copper or aluminum, which have good thermal conductivity.
[0099] The electronic component 3 is, for example, a semiconductor element such as a BGA, and is mounted on the wiring board 6. The tip surface of the side wall 2b of the heat spreader 2 is also mounted on the wiring board 6, so that the side wall 2b surrounds the electronic component 3 at a predetermined distance. By providing the laminate 7 of the present invention on the main surface 2a of the heat spreader 2, a heat dissipation member that absorbs heat generated by the electronic component 3 and dissipates the heat from the heat sink 5 is formed. EXAMPLES
[0100] Examples of the present invention will be described below, but the present invention is not limited to these examples.
[0101] <Synthesis of hardener> A polyfunctional carboxylic acid represented by the above general formula (1) was synthesized as a curing agent by the following procedure, and was identified. 50 parts by mass of glycerin (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was weighed into a three-necked glass flask equipped with a thermocouple, a stirrer, a cooling tube, and a heating device, and 43.3 parts by mass of methyl ethyl ketone (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added thereto and thoroughly stirred to completely dissolve. Next, 1 part by mass of triethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) was added as a catalyst and further stirred thoroughly. After complete dissolution, 50 parts by mass of glutaric anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.) represented by the following structural formula was added dropwise in powder form into the three-necked flask using a funnel. The above was kept constant at 60°C and stirred for 24 hours until the reaction was completely completed. After cooling to room temperature, the above synthesis product was transferred to an eggplant flask and concentrated with an evaporator, and then dried under reduced pressure (60°C for 24 hours) to obtain the desired polyfunctional carboxylic acid in a yield of 90%. The obtained polyfunctional carboxylic acid was in liquid form.
[0102] The obtained polyfunctional carboxylic acid was identified by FT-IR measurement. FT-IR measurement was performed by ATR method using Nicolet iS10 (manufactured by Thermo Fisher Scientific Co., Ltd.). FTIR absorption of the obtained polyfunctional carboxylic acid is shown below. 781cm -1 , 868cm -1 , 1016cm -1 , 1065cm -1 , 1097cm -1 , 1138cm -1 , 1268cm -1 , 1410cm -1 , 1703cm -1 , 1730cm -1 and 2700 cm -1 ~3700cm -1 .
[0103] As a result of FTIR absorption, broad absorption vibrations derived from carboxylic acid were observed, and it was determined that the target compound was pentanedioic acid-1,1',1''-(1,2,3-propanetriyl) ester having the following structure (molecular formula: C 18 H 26 O 12 ) was found to be obtained.
[0104] [ka]
[0105] Example 1 <Preparation of Thermally Conductive Layer Composition> The compositions and contents shown in Table 1 were mixed uniformly using a stirring device (Awatori Rentaro Automatic Revolving Mixer, manufactured by Thinky Corporation) to prepare a first thermal conductive layer composition and a second thermal conductive layer composition. The content of each component in Tables 1 and 2 is in volume percent. The Novacure (registered trademark) series used contains an epoxy resin in addition to an epoxy resin curing agent, as shown in the "epoxy resin curing agent" column.
[0106] <Manufacture of Laminate> Next, a first thermally conductive layer composition was applied onto a substrate (silicon substrate) measuring 20 mm x 20 mm x 0.725 mm so that the average thickness after curing would be 20 μm, and then a second thermally conductive layer composition was applied onto the first thermally conductive layer so that the average thickness after curing would be 80 μm. A counter substrate (copper) measuring 20 mm x 20 mm x 1 mm was laminated onto this second thermally conductive layer composition, and the resultant was heated and cured in two stages, at 150°C for 5 minutes and at 170°C for 60 minutes, to produce the laminate of Example 1.
[0107] (Examples 2 to 5) The laminates of Examples 2 to 5 were each produced in the same manner as in Example 1, except that the contents of the curing agent, curing component, and thermoplastic resin in the second thermal conductive layer composition used in Example 1 were changed to change the area ratio of the alloy layer to the substrate interface and the presence or absence of a resin layer at the substrate interface.
[0108] Comparative Example 1 The laminate of Comparative Example 1 was manufactured in the same manner as in Example 1, except that the contents of the curing agent, curing component, and thermoplastic resin in the second thermal conductive layer composition used in Example 1 were changed so that the area ratio of the alloy layer to the substrate interface was 0% and the entire substrate interface was made into a resin layer.
[0109] (Comparative Examples 2 to 3) Laminates of Comparative Examples 2 and 3 were produced in the same manner as in Example 1, except that the composition of the first thermal conductive layer composition in Example 1 was changed as shown in Table 2.
[0110] Next, for Examples 1 to 3 and Comparative Examples 1 to 3, "Evaluation of the presence or absence of alloy layer formation," "Measurement of the average thickness of each layer," "Measurement of the area ratio of the alloy layer to the substrate interface," "Thermal conductivity," and "Adhesion" were evaluated as follows. The results are shown in Tables 1 and 2.
[0111] <Evaluation of the presence or absence of alloy layer formation> Each laminate was cut, and the cut surface was polished. The polished surface was photographed with a scanning electron microscope (S-3000N, manufactured by Hitachi, Ltd.) to observe the presence or absence of an alloy layer (metal alloy phase) formed by the low-melting point metal and thermally conductive particles 1. The presence or absence of the formation of an alloy layer was evaluated according to the following criteria. [Evaluation Criteria] ◯: The low-melting point metal particles melted and formed an alloy. ×: The low melting point metal particles are not melted and no alloy is formed.
[0112] <Measurement of the average thickness of each layer> Next, the thickness of each layer was measured from the cut surface of the laminate, and the average value of the thicknesses at any three points was calculated. It was confirmed that each of the laminates of Examples 1 to 3 had an alloy layer, a second thermally conductive layer, and an opposing substrate on a substrate in this order, corresponding to the cross-sectional view of the laminate shown in Figure 2.
[0113] As a result, the total average thickness of the alloy layer and the first thermally conductive layer was 20 μm, and the average thickness of the second thermally conductive layer was 80 μm in all of Examples 1 to 3 and Comparative Examples 1 to 3. In addition, the average thickness of the alloy layer was measured, and the ratio of the average thickness of the alloy layer to the total average thickness of the first thermally conductive layer and the alloy layer was calculated and shown in Tables 1 and 2.
[0114] <Measurement of the area ratio of the alloy layer to the substrate interface> The interface between the substrate and the thermally conductive layer, which is a cured product of the thermally conductive composition, was photographed from the substrate side of the laminate using an infrared microscope (MX63, manufactured by Olympus Corporation) and an InGaAs camera (C12741-03, manufactured by Hamamatsu Photonics Co., Ltd.) The image of the alloy layer, i.e., the alloyed portion where the alloy was formed, was binarized to distinguish it from the portion other than the alloy layer, and the area of the alloy layer was calculated. The area in the image was calculated using Excel made by Microsoft Corp. The binary bitmap image created was loaded into Excel, and the number of pixels in the entire image corresponding to the area of the substrate interface and the number of pixels in the alloyed portion corresponding to the area of the alloy layer were obtained. The area ratio (%) of the alloy layer to the substrate interface was calculated based on the following formula (1), and is shown in Tables 1 and 2. (Formula 1) Area ratio of alloy layer to substrate interface (%) = (Number of pixels in alloyed area / total number of pixels) x 100
[0115] <Thermal conductivity> <<Preparation of laminated body after compression>> Each laminate was sandwiched between a 20 mm x 20 mm square silicon plate (thickness 0.77 mm) and a 20 mm diameter copper plate (thickness 1.0 mm) and pressed for 5 minutes using a mini press under the following conditions: upper plate temperature on the copper substrate side was 150°C, lower plate temperature on the silicon substrate side was 150°C, and set air pressure was 0.11 MPa (40 psi in terms of pressure).
[0116] <<Preparation of laminate after reflow>> The low melting point metal particles of each laminate were remelted (reflowed) by performing a treatment simulating reflow conditions, in which heating was performed at 260° C. for 5 minutes, to obtain a laminate after reflow.
[0117] <<Evaluation of thermal conductivity>> The thermal resistance (℃ cm) of the laminate after compression and the laminate after reflow (interface Cu and silicon) was measured using a method in accordance with ASTM-D5470. 2 The thermal resistance of the laminate was calculated by subtracting the thermal resistance of the substrate (silicon substrate) and the opposing substrate (copper substrate) from the results, and the thermal resistance of the portion excluding the substrate and the opposing substrate from the laminate was calculated. The thermal conductivity (W / m K) was calculated from this thermal resistance and the thickness (100 μm) of the portion excluding the substrate and the opposing substrate from the laminate, and the thermal conductivity was evaluated according to the following criteria. [Evaluation Criteria] ◎: Thermal conductivity is 20 W / m K or higher. Good: Thermal conductivity is 12 W / m K or more and less than 20 W / m K. ×: Thermal conductivity is less than 12 W / m K.
[0118] <Adhesiveness> For each Example, the adhesiveness was evaluated by the following procedure using the laminate after compression bonding and the laminate after reflow. The laminate after compression bonding and the laminate after reflow were prepared according to the procedure explained in the above section on <Thermal Conductivity>. As a reliability test, a bond tester (4000Plus, manufactured by Nordson DAGE) was used to perform a shear test on the laminate after compression bonding or the laminate after reflow under the test conditions of a shear rate of 200 μm, height of 150 μm, n=3, and an environment of 130°C, and the adhesion at high temperatures was evaluated. [Evaluation Criteria] ◯: The adhesive strength is 3 kg or more. ×: The adhesive strength is less than 3 kg.
[0119] [Table 1]
[0120] [Table 2]
[0121] As a result, in the laminate of Example 1, it was confirmed that the molten low-melting point metal in the second thermal conductive layer composition flows into the first thermal conductive layer composition together with the curing agent, and an alloy layer is formed by the reaction between the low-melting point metal and the first thermal conductive particles, and the area ratio of the alloy layer to the substrate interface was 6%. No resin layer was present at the substrate interface, and the first thermal conductive layer, which was the cured first thermal conductive layer composition, was formed in the area other than the alloy layer (see FIG. 3 and FIG. 6 described later). The laminate of Example 1 had good thermal conductivity and adhesiveness after compression bonding. It was also found that the laminate after reflow had good thermal conductivity and adhesiveness, and was also excellent in heat resistance.
[0122] 6 to 10 and 11 are schematic diagrams showing the substrate interface in the laminates of Examples 1 to 5 and Comparative Example 1. These are schematic diagrams showing the presence or absence of alloy layer 13, first thermally conductive layer 12, and resin layer 16 and their respective area ratios with reference to the results of evaluation by the above <Measurement of Area Ratio of Alloy Layer to Substrate Interface>, and differ from the actual shapes of the alloy layer etc. at the substrate interface.
[0123] From Examples 1 to 5, it was found that the area ratio of the alloy layer to the substrate interface could be adjusted by adjusting conditions such as the content of the curing agent. In comparison with Example 1 (see Figs. 3 and 6), when the amount of the curing agent was increased, the area ratio of the first thermally conductive layer 12 to the substrate interface decreased, and the area ratio of the alloy layer 13 to the substrate interface increased (Example 2, see Figs. 3 and 7; Example 3, see Figs. 2 and 8). When the amount of the curing agent was further increased, the area ratio of the alloy layer 13 to the substrate interface decreased, and the area ratio of the resin layer 16 to the substrate interface increased (Example 4, see Figs. 4 and 9; Example 5, see Figs. 4 and 9). Then, the area ratio of the resin layer 16 to the substrate interface became 100% (Comparative Example 1, see Figs. 11 and 12).
[0124] In Examples 2 and 3, in which the amount of the curing agent in the second thermally conductive layer composition was changed, the area ratio of the alloy layer to the substrate interface was 53% and 100%, respectively. That is, in Example 2, the resin layer was not present at the substrate interface, and the first thermally conductive layer was formed in the area other than the alloy layer. In Example 3, the resin layer and the first thermally conductive layer were not present at the substrate interface, and the alloy layer was 100%. It was found that Examples 2 and 3 also exhibited excellent heat resistance, thermal conductivity, and adhesion, similar to Example 1.
[0125] In Examples 4 to 5, in which the amount of the curing agent in the second thermal conductive layer composition was further changed, the area ratio of the alloy layer to the substrate interface was 51% and 5%, respectively, and a resin layer derived from the excess curing agent flowing in from the second thermal conductive layer composition was formed at the substrate interface in addition to the alloy layer. It was found that Examples 4 to 5 also showed excellent heat resistance, thermal conductivity, and adhesion similar to Example 1 as long as the alloy layer was present at the substrate interface.
[0126] On the other hand, in the laminate of Comparative Example 1, in which an even more excessive amount of curing agent was used than in Examples 1 to 5, the first thermal conductive layer composition was entirely converted into an alloy layer. In addition, as shown in Figs. 11 and 12, in the laminate 20 of Comparative Example 1, a resin layer 16 derived from the excess curing agent flowing from the second thermal conductive layer composition was formed over the entire surface of the interface with the substrate 11. This resulted in a decrease in thermal conductivity. In addition, the adhesiveness and heat resistance due to reflow treatment were also poor.
[0127] In the laminate of Comparative Example 2, since the first thermally conductive layer contains a low-melting point metal, the thermal conductivity and adhesion of the laminate after compression bonding met the evaluation criteria, but the thermal conductivity and adhesion after reflow were poor, resulting in poor heat resistance. In addition, in the laminate of Comparative Example 3, the first thermal conductive layer composition did not contain low-melting point metal particles, but also did not contain an epoxy resin curing agent, resulting in poor heat resistance, thermal conductivity, and adhesion. In the laminates of Comparative Examples 2 and 3, the first thermal conductive layer composition did not contain an epoxy resin curing agent, so it took time for the first thermal conductive layer composition to harden, and the layer structure between the first thermal conductive layer and the alloy layer and their interface (see Figure 2), as observed in the laminate of Example 1, could not be observed in the laminates of Comparative Examples 2 and 3.
[0128] Details of each component in Tables 1 and 2 are as follows.
[0129] -Epoxy resin- EPICLON (registered trademark) EXA-850CRP (manufactured by DIC Corporation)
[0130] -Epoxy resin hardener- Epoxy resin hardener: Novacure (registered trademark) HX-3941HP (manufactured by Asahi Kasei E-Materials Corporation, epoxy resin hardener 30% to 40%, bisphenol A type epoxy resin 45% to 55%, bisphenol F type epoxy resin 10% to 20%)
[0131] -Curing component- Curing component (oxetane compound): ETERNACOLL (registered trademark) OXBP (manufactured by Ube Industries, Ltd.), 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl
[0132] - Hardener - Curing agent: polyfunctional carboxylic acid (pentanedioic acid-1,1',1''-(1,2,3-propanetriyl) ester represented by the above general formula (1); molecular formula: C 18 H 26 O 12 ;Dexerials Corporation synthetic product)
[0133] -Low melting point metal particles (solder particles)- Sn 58 Bi 42 Manufactured by Mitsui Mining & Smelting Co., Ltd., Volume average particle size Dv: 4μm, Melting point 139℃
[0134] -Thermal conductive particles- Thermally conductive particles 1: Ag particles, manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1.9 μm Thermally conductive particles 2: Ag-coated Cu particles, manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size Dv: 10 μm
[0135] -Thermoplastic resin- Thermoplastic resin: YP-50 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), polyhydroxy polyether synthesized from bisphenols and epichlorohydrin [Industrial Applicability]
[0136] The laminate of the present invention can achieve excellent heat resistance, thermal conductivity, and adhesion as a thermal interface material (TIM), and is therefore suitable for use in, for example, the vicinity of various electric devices such as CPUs, MPUs, power transistors, LEDs, and laser diodes, whose element operation efficiency, life span, and the like are adversely affected by temperature. [Explanation of symbols]
[0137] 1. Thermal conductive sheet 2 Heat spreader 2a Main surface 3 Heating elements (electronic components) 3a Top side 5. Heat sink 6 Wiring board 7 Laminate 10 Laminate 10a Laminate before curing 11 Base material 12 First heat conductive layer 12a First thermally conductive layer composition 12b First thermally conductive particles 13 Alloy layer 13b alloy 14 Second heat conducting layer 14a Second thermally conductive layer composition 14b Second thermally conductive particles 14c Low melting point metal particles 14d Low melting point metals 15 Opposing substrate 16 Resin layer
Claims
1. A substrate; an alloy layer provided on the base material, the alloy layer including an epoxy resin, an epoxy resin curing agent, first thermally conductive particles, and an alloy of a low-melting point metal and the first thermally conductive particles; a second thermally conductive layer provided on the alloy layer, the second thermally conductive layer including a hardening component, a hardening agent for hardening the hardening component, second thermally conductive particles, and the low-melting point metal; an area ratio of the alloy layer to the interface of the substrate is 1% or more and 100% or less; A laminate, wherein the alloy layer does not contain the low-melting point metal.
2. The laminate according to claim 1 , further comprising a first thermally conductive layer containing the epoxy resin, the epoxy resin curing agent, and the first thermally conductive particles, but not containing the low-melting point metal.
3. The laminate according to claim 1 , wherein the curing agent is represented by at least one of the following general formula (1) and general formula (2): 【Chemistry 1】 In the above general formula (1), R 1 ~R 3 R each independently represents a hydrogen atom, an alkyl group, or a caprolactone skeleton. 4 R represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group. 5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms. 【Chemistry 2】 In the above general formula (2), R 1 and R 2 R each independently represents a hydrogen atom, an alkyl group, or a caprolactone skeleton. 4 and R 6 R each independently represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group. 5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.
4. The laminate according to claim 1 , wherein the curing component comprises at least one of an oxetane compound and an epoxy resin.
5. The laminate according to claim 1 , wherein the first thermally conductive particles include at least one of silver particles, silver-coated particles, and silver particles.
6. The laminate according to claim 1 , wherein the low melting point metal comprises Sn and at least one selected from the group consisting of Bi, Ag, Cu, and In.
7. 3. The laminate according to claim 1, wherein the substrate comprises at least one material selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
8. The laminate according to claim 1 , wherein the content of the first thermally conductive particles in the alloy layer is 50% by volume or more.
9. a facing substrate on the second thermally conductive layer, the facing substrate facing the substrate; The laminate according to claim 1 , wherein the opposing substrate comprises at least one selected from the group consisting of copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
10. applying a first thermally conductive layer composition onto a substrate, the first thermally conductive layer composition including an epoxy resin, an epoxy resin curing agent, and first thermally conductive particles, and including no low melting point metal; applying a second thermally conductive layer composition onto the applied first thermally conductive layer composition, the second thermally conductive layer composition including a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting point metal particles; and heating the first thermally conductive layer composition and the second thermally conductive layer composition to form an alloy layer formed by the low-melting point metal of the low-melting point metal particles melting and reacting with the first thermally conductive particles, and a second thermally conductive layer. A method for producing a laminate, wherein an area ratio of the alloy layer to an interface of the substrate is 1% or more and 100% or less.
Citation Information
Patent Citations
Thermally conductive adhesive
JP2012188646A